P87 | EVALUATION OF SPEXIN AND KISSPEPTIN EXPRESSIONS IN ADIPOSE TISSUES OF WISTAR ALBINO RATS DURING PUBERTY (European Journal of Histochemistry)
Spexin (SPX) and Kisspeptin (KISS) are peptides implicated in regulating metabolism and reproduction. White adipose tissue (WAT) and brown adipose tissue (BAT) play distinct roles in lipid metabolism, with BAT activity potentially increasing during adolescence. This study investigates the relationship between pubertal status and SPX/KISS expression in female rat adipose tissues. To evaluate SPX and KISS expression levels in serum, WAT, and BAT of female Wistar Albino rats in relation to pubertal status. Serum and adipose tissue samples were collected from prepubertal (n=10, postnatal day 28) and pubertal (n=10, postnatal day 42) female Wistar rats. Serum was analyzed for SPX, KISS, glucose and insulin. Homeostasis-model assessment-insulin resistance (HOMA-IR) was calculated. SPX and KISS protein expression in WAT and BAT was assessed using immunohistochemistry and quantified with ImageJ. SPX and KISS1 mRNA expression in WAT and BAT were analyzed using qRT-PCR. Statistical significance was defined as p<0.05. The weight-to-birth weight ratio and HOMA-IR were significantly higher in pubertal rats (p <0.001 and p=0.018, respectively). Serum SPX levels were significantly lower in pubertal rats (p=0.029), while KISS1 showed a decreasing trend (p=0.07). SPX staining intensity was significantly reduced in WAT (p=0.019) and significantly increased in BAT (p<0.001) of pubertal female rats. SPX mRNA expression was lower in WAT (p=0.047) of pubertal rats. KISS1 mRNA expression also decreased, though not significantly (p=0.06). Puberty in female rats is associated with decreased serum SPX, decreased SPX expression in WAT, and increased SPX expression in BAT. Increased BAT SPX expression during puberty may relate to reported changes in BAT volume during this developmental stage.